(untitled) (Journal of Legal Studies, 2018)
The legal terminology represents a specialised language by which both the lawmaker and the person implementing the law focus on a pre-established communication channel which guarantee for the stability, the accessibility and the predictability of the law, as well as on the juridical security. In the situations when the law moves away from various reasons from the unanimously agreed meaning, imbalances are triggered in practice. In order to re-establish the balance of the law, the Constitutional Court intervenes in decisive situations. Thus, our instance of constitutional contentious has been seized on the exception of non-Constitutionality of the provisions of the art. 249 par. (1) of the Criminal Law in 1969 and of the art. 298 of the Criminal Law. The authors of the exception asked the Court to notice that the provisions of the art. 298 of the Criminal Law are constitutional only in the measure when the phrase "it fails to accomplish it" from their contents mean "it accomplishes it by breaking the law".